Reflections on economic growth in Antigua and Barbuda - Nicholls, Garth (2001)
Argues that the economic turnaround of Antigua can be accounted for by at least the four following factors: tourism; a land lease program; the policy stance of the Antiguan government regarding Foreign Direct Investment -FDI; and package tourism.